Gastrointestinal Cancers and Liver Cirrhosis: Implications on Treatments and Prognosis - Xiang, Ze; Li, Yiqi; Zhu, Chaojie; Hong, Tu; He, Xianglin; Zhu, Hua; Jiang, Danbin (Frontiers in Oncology, 2021)
Liver cirrhosis, a common complication of gastrointestinal cancer, tends to increase the risk of gastrointestinal tumors. Patients with gastrointestinal cancer and cirrhosis often have serious postoperative complications and poor prognosis after surgery. Multiple studies have shown that the gastrointestinal cancer stage and the cirrhosis grade can influence surgical options and postoperative complications. The more severe the stage of cancer and the degree of cirrhosis, the more limited the surgical options and the higher the risk of postoperative complications. Therefore, in the treatment of patients with gastrointestinal cancer and cirrhosis, doctors should comprehensively consider the cancer stage, cirrhosis grade, and possible postoperative complications. This review summarizes the treatment methods of patients with different gastrointestinal cancer complicated with cirrhosis.